2019
DOI: 10.1021/acs.orglett.9b03040
|View full text |Cite
|
Sign up to set email alerts
|

Two Trifunctional Leloir Glycosyltransferases as Biocatalysts for Natural Products Glycodiversification

Abstract: Two promiscuous Bacillus licheniformis glycosyltransferases, YdhE and YojK, exhibited prominent stereospecific but nonregiospecific glycosylation activity of 20 different classes of 59 structurally different natural and non-natural products. Both enzymes transferred various sugars at three nucleophilic groups (OH, NH2, SH) of diverse compounds to produce O-, N-, and S-glycosides. The enzymes also displayed a catalytic reversibility potential for a one-pot transglycosylation, thus bestowing a cost-effective app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Differentiation between 4′‐ O ‐ and 5‐ O ‐glycosylation sites can be performed on the basis of the fragmentation of [M + H] + ions. Namely, the loss of sugar moiety from position 4′ occurs with similar efficiency to the loss of sugar moiety from position 7 3,39,40 . Therefore, it is definitely a less efficient process than the loss of sugar moiety from position 5.…”
Section: Resultsmentioning
confidence: 99%
“…Differentiation between 4′‐ O ‐ and 5‐ O ‐glycosylation sites can be performed on the basis of the fragmentation of [M + H] + ions. Namely, the loss of sugar moiety from position 4′ occurs with similar efficiency to the loss of sugar moiety from position 7 3,39,40 . Therefore, it is definitely a less efficient process than the loss of sugar moiety from position 5.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the discovery of the potential pharmacological activity of these three chalcone glucosides becomes possible. Compared with GTs from plants, microbial GTs generally exhibit remarkable substrate universality [13,14]. Our previous study has proved that BsGT1 from B. subtilis ATCC 6633 had excellent glycosylation ability toward curcumin and analogs [9].…”
Section: Discussionmentioning
confidence: 99%
“…While there have been numerous studies on glycosylation, particularly flavonoids O -glucosides and C -glucosides, very few studies on N -glucosides have been reported [ 16 ]. Recently, our group has explored the N -glycosyltransferase activity of YdhE [ 17 ], which has been observed to have the potential to serve as an important platform for the biosynthesis of bioactive N -glycosylated compounds ( Figure 1 ). However, in vitro enzymatic catalysis requires equimolar amounts of expensive uridine diphosphate (UDP)-sugar which is not feasible economically on a large-scale production.…”
Section: Introductionmentioning
confidence: 99%